2020
DOI: 10.24912/jm.v24i1.618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competence and Career Development on Turnover and It’s Impact on Productivity

Abstract: The purpose of this study was to determine the effect of competency on turnover, to determine the effect of career development on turnover, to determine the effect of competencyand career developmentsimultaneously on turnover, to determine the effect of competence on productivity, to determine the effect of career development on productivity, to determine the effect of competencyand career developmentsimultaneously on productivity, to find the effect of turnover on productivity at PT. Reckitt Benckiser Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…If they perceive that yours offers them better competency development, they will stay with the organization. Hira and Rusilowati (2020) studied the effect of competence development and career development on turnover intentions and concluded that both have a negative and significant effect. Additionally, it was discovered in a study by Martini et al (2023) that employee competency development had a negative and significant impact on turnover intentions.…”
Section: Organizational Competence Development Practices and Turnover...mentioning
confidence: 99%
“…If they perceive that yours offers them better competency development, they will stay with the organization. Hira and Rusilowati (2020) studied the effect of competence development and career development on turnover intentions and concluded that both have a negative and significant effect. Additionally, it was discovered in a study by Martini et al (2023) that employee competency development had a negative and significant impact on turnover intentions.…”
Section: Organizational Competence Development Practices and Turnover...mentioning
confidence: 99%
“…To ensure that employees have the quality and competence that organizations need, there should be processes to help employees remain competitive in a healthy way (Rusilowati & Maulida, 2020). Organizations should focus on healthy competition amongst employees which can be created through competency determination and positive career development as both do enhance organizational productivity (Hasan et al, 2020).…”
Section: Resiliencementioning
confidence: 99%